The impact on organisational performance as a result of investment in self-service technology within the South African financial services industry - Leak, Gerald (Department of Information Systems, 2017)
The advent of self-service technology (SST) and the adoption thereof has occurred in many industries and sectors globally. The financial services and banking sector embraced the SST transformation and invested heavily into this channel including the South African industry. This study aims to understand the causal relationship between the investment into the SST channel and the impact it has on organisational performance within the South African context. This research exercise applied a single unit of analysis case study research strategy to examine the impact on the organisation's various performance criteria, namely profitability, productivity, cost efficiency and intangible benefits as a result of a SST investment strategy. Qualitative data was collected from interviews with key informants from the selected organisation and analysed thematically. The study adopted a theory based deductive approach using the DeLone and McLean model of IS success (2003) as its underlying research framework. The findings of this study deduced that with an appropriate investment strategy in SSTs, there would be a positive impact on the net benefits of the organisation with an explicit relationship dynamic. This study lends support to earlier studies of this nature, particularly with regard to the SST channel offering, as there is a lack of literature due to the evolution of perception and recency of this technology channel. The relationship dynamic aspects between the constructs of this study also contributes to the closing of gaps within the body of knowledge that exists. However it must be noted that these findings are based on a single unit of analysis case study research strategy which connotes limitations in terms of generalisations.